2022
DOI: 10.21203/rs.3.rs-2394336/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Passive segregation and multi-scale space-use adjustments to socio-ecological variables in western gorillas

Abstract: Understanding what are the proximate mechanisms shaping species’ space-use dynamics, and at which scale, can provide insights into species socio-ecology. This is crucial information for both applied (e.g., conservation) and theoretical questions (e.g. individuals’ coexistence/segregation). Yet, longitudinal views of the space-use dynamics of animal species are generally lacking. Taking advantage of an unprecedented long-term data set (up to 8 years) on ranging patterns of wild western gorillas (Gorilla gorilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 105 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…However, trends in female‐specific feeding competition on ranging were not detected. Other investigations on a different western lowland gorilla population found that female nutritional requirements and intragroup feeding competition influenced group‐ranging dynamics, such as increased daily path length with the number of females with dependent offspring (Robira et al, 2022). More direct measures on female feeding competition may better clarify female‐specific effects on ranging dynamics in this population.…”
Section: Discussionmentioning
confidence: 99%
“…However, trends in female‐specific feeding competition on ranging were not detected. Other investigations on a different western lowland gorilla population found that female nutritional requirements and intragroup feeding competition influenced group‐ranging dynamics, such as increased daily path length with the number of females with dependent offspring (Robira et al, 2022). More direct measures on female feeding competition may better clarify female‐specific effects on ranging dynamics in this population.…”
Section: Discussionmentioning
confidence: 99%
“…However, the abundance of fruit varies throughout the year, as does their diet, which changes from high to low frugivory (Remis, 1997). These variations are mimicked by oscillations in their activity, the distance they travel, and the area they cover per day (Doran-Sheehy et al, 2004;Masi et al, 2009;Robira et al, 2023b). None of these possibilities occurred in this model.…”
Section: Movement As a Multifaceted Behavioural Traitmentioning
confidence: 93%
“…However, while foragers' cognition is likely to be shaped by the distribution of resources (Boyer & Walsh, 2010;Bracis et al, 2015;Grove, 2013;Milton, 1981;Robira et al, 2021), the characteristics of the resources themselves could be the result of forager-induced selection (Lomáscolo & Schaefer, 2010;Rojas et al, 2021;Soldati et al, 2015). In the tropical rainforests, for example, the cognition of frugivorous primates has probably been shaped by the challenge of the ephemerality and dispersion of their food (Milton, 1981;Trapanese et al, 2019a;Zuberbühler & Janmaat, 2010), supporting complex (Janmaat et al, 2013;Janson, 1998Janson, , 2016Robira et al, 2023a;Teichroeb & Vining, 2019;Trapanese et al, 2019b) and versatile (Janmaat et al, 2006;Robira et al, 2023b;Trapanese et al, 2022) movement heuristics. In turn, primates remember and forage for the most rewarding plants (Ban et al, 2014;Ban et al, 2016;Flörchinger et al, 2010).…”
mentioning
confidence: 99%